APC-Verwaltung im institutionellen Repositorium - Wagner, Alexander (GMS Medizin – Bibliothek – Information, 2018)
Management of publication charges is one of the big challenges at scientific institutions. Due to the significant increase of publications that are funded via article processing charges in the gold open access area, a neccessity arises to establish systems for handling these. Beyond simple management of the charges, a general goal should be to increase the visibility of the publications as well as of the research output of the affiliate institutions. Thus it seems logical that especially publications that were published at substantial costs should be accessible via the originating institutions themselves. Usually, this involves institutional open access repositories. In some cases, e.g. among the JOIN² partners, these repositories are at the same time the relevant source for scientific reporting and the institutional bibliography. As these systems already process high-quality article-level bibliographic data, it seems reasonable to use these systems to manage and monitor article processing charges as well. This also reduces redundancies and inconsistencies while increasing completeness. Furthermore, the usage of well-known repository software allows for an easy data exchange and re-use via standardized, established interfaces. For example, OAI-PMH can be used to make publication charges available for aggregation in an automatized manner, e.g. by OpenAPC, which helps promote market transparency. At approximately the same time, these conclusions were drawn independently at the university library Regensburg and at JOIN². We introduce the respective solutions based on EPrints in Regensburg and INVENIO at JOIN² and show procedures for automatized data delivery to OpenAPC.